Child healthcare nurses believe that bilingual children show slower language development, simplify screening procedures and delay referrals. (24th November 2014) - Nayeb, Laleh; Wallby, Thomas; Westerlund, Monica; Salameh, Eva‐Kristina; Sarkadi, Anna
Abstract Aim A significant number of children living in Sweden are bilingual, but how language screening is performed in this group is unknown. We investigated child healthcare nurses' perceptions of the language screening of bilingual children aged 30–36 months, together with their clinical practices. Methods An online questionnaire was completed by 863 nurses who performed language screening of bilingual children in Sweden at least once a month, corresponding to 89% of the target population. Cox regression identified predictors of the nurses' tendency to simplify the screening of bilingual children. Results The nurses reported a greater lack of confidence and more difficulties in interpreting screening outcomes for bilingual than monolingual children (p < 0.001). Half of the nurses simplified the screening processes for bilingual children and 74% postponed referrals to speech and language services, basing these adaptations on their perceptions of the children's Swedish language skills (p < 0.001). Most nurses (82%) believed that language development was slower in bilingual children, and this was the strongest predictor of simplified screening practices (RR=2.00, 95% CI 1.44–2.77). Conclusion Child healthcare nurses need easily accessible information and clear guidelines on the language development of bilingual children to ensure that bilingual and monolingual children receive equitable language screening services.